Nursing, Indigenous Health, Water, and Climate Change - Darlene Sanderson; Noeman Mirza; Mona Polacca; Andrea Kennedy; R. Lisa Bourque-Bearskin (York University Libraries, 2020)
Nurses have a duty to uphold the right to health. Clean water is vital for health as an inclusive right for all people, yet access is threatened by climate change. Complex impacts of colonization on climate change has resulted in two key problems: lack of clean water access by Indigenous Peoples and marginalization of Indigenous traditional teachings that support water protection. Indigenous teachings of living in harmony with Mother Earth are important contributions to global water policy and health solutions.  Indigenous traditional laws on water protection may be understood through Indigenous water declarations. Nurses have an important opportunity to respect traditional teachings noting interconnections of health, water, and climate change to advance health. Water is life.